Introduction to jurisprudence: legal theory - Tripathi, Bijai Narain Mani (Allahabad, 1980)
The author has great pleasure in presenting eighth Edition of the book. The present edition has been extensively revised. It incorporates the developments which have taken place with respect to the legal principles in recent times. This edition further tends to give the subject an Indian orientation. The last Part i.c. Part Fifth which was added in the book in the last edition, has been made up-to-date. In this edition the emerging features of the National Jurisprudence have been boldly underlined.
Keywords: Jurisprudence history